Escola religiosa e produções de subjetividades : relações de gênero e sexualidade em um currículo escolar - Oliveira, Cristiano José de (2016)
This dissertation aims to analyze the productions of teaching and student subjectivities in a religious school curriculum, taking relations of gender, body and sexuality as analytical categories. Field research was carried out at ‗Nossa Senhora‘ High School (Our Lady), a school in the interior of Sergipe, founded in the mid-twentieth century, with a Catholic religious background and always coordinated by Nuns. In it, through the analysis of pedagogical documents, oral histories about the school were searched, and teachers‘ narratives about episodes that occurred and occur in that school. From this material, three sections were constructed in order to meet the research objectives. The first section discusses the main theoretical and analytical categories that underlie this research – such as gender, sexuality, curriculum and queer studies – presents the methodological procedures, maps the academic production in this theme and contextualizes the object of studies of this dissertation. In the second section, the analyzes focus on the production of regulated, silenced, and transgressive sexualities in the curriculum investigated. Here, the subjectivity of non-confrontation and the hetero-regulated subjectivity are described and analyzed. In the third section, the data from the research are presented, which show how gender relations are established and the effects on generalized subjects. Before the analysis of the narratives, it was noticed that despite the norms, regulations, surveillance of students and students, subversions were evidenced that arise in a process of transgression to the religious and biological discourse regarding gender and sexuality.